Investigating the Effect of Temperature and Time of the Process of Producing Graphene Quantum Dots by Carbonization on Structural, Microstructural, and Optical Properties - M. Nazari; H. R. Baharvandi; N. Ehsani (Journal of Advanced Materials in Engineering)
Graphene quantum dots are a new member of the carbon family with various applications rapidly developing due to their unique properties. This research aims to obtain this valuable nanomaterial using a convenient, quick, and easy production method called carburizing. For this purpose, production from the primary source of glutamic acid was done at temperatures of 210, 220, and 230 ºC and times of 60 and 90 s. Next, the Raman test and fourier transform infrared spectroscopy, dynamic light scattering, photoluminescence, and ultraviolet-visible spectroscopy were performed to investigate the properties of graphene quantum dots of the product. The microstructure was examined by field emission escanning electron microscopy images. Also, the morphology of the surface and the distance between the planes were investigated by high resolution transmission electron microscopy. The results showed that the best sample in terms of distribution and particle size was production at 220°C for 60 s with 3 nm in particle size for over 45% of the particles. Moreover, the highest absorption intensity in this sample was appeard at the wavelength of 244 nm. An increase in the production time caused the graphene quantum dots to be coarser with greater dispersion in particle size distribution. Photoluminescence studies in the excitation wavelength range of 340-400 nm revealed the appearance of a strong peak in the sample produced at 220 ºC and calcination time 60 s at the excitation wavelength of 380 nm.